Starch-Branching Enzyme I-Deficient Mutation Specifically Affects the Structure and Properties of Starch in Rice Endosperm - Satoh, Hikaru (The American Society for Plant Biologists, 2003)
We have isolated a starch mutant that was deficient in starch-branching enzyme I (BEI) from the endosperm mutant stocks of rice (Oryza sativa) induced by the treatment of fertilized egg cells with N-methyl-N-nitrosourea. The deficiency of BEI in this mutant was controlled by a single recessive gene, tentatively designated as starch-branching enzyme mutant 1 (sbe1). The mutant endosperm exhibited the normal phenotype and contained the same amount of starch as the wild type. However, the mutation apparently altered the fine structure of amylopectin. The mutant amylopectin was characterized by significant decrease in both long chains with degree of polymerization (DP) ≥ 37 and short chains with DP 12 to 21, marked increase in short chains with DP ≤ 10 (A chains), and slight increase in intermediate chains with DP 24 to 34, suggesting that BEI specifically synthesizes B(1) and B(2–3) chains. The endosperm starch from the sbe1 mutant had a lower onset concentration for urea gelatinization and a lower onset temperature for thermo-gelatinization compared with the wild type, indicating that the genetic modification of amylopectin fine structure is responsible for changes in physicochemical properties of sbe1 starch.